Peran Etika Filsafat Pendidikan dalam Membentuk Karakter dan Nilai Moral Peserta Didik - Ayu Safitri; Desty Endrawati Subroto; Safriyah Safriyah; Siti Nurhalisa (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Ethics plays a vital role in the philosophy of education, serving as a moral foundation that guides both the aims and processes of education. Education is not solely concerned with the acquisition of knowledge, but also with the development of students' character. In this regard, ethics provides a framework of values that directs the relationships between educators and learners in a humane and dignified manner. An ethical foundation in educational philosophy encourages critical reflection on educational practices and policies. Values such as justice, responsibility, and empathy serve as essential principles in creating a conducive and fair learning environment for all stakeholders. Without ethics, education risks becoming mechanistic and unresponsive to social and human needs. Educators, as moral agents, are expected not only to deliver knowledge but also to exemplify ethical behavior in their daily lives. Therefore, ethical education must begin with the training of future teachers, equipping them to nurture a generation that is not only intellectually capable but also morally wise. In this way, ethics in the philosophy of education becomes a central pillar in building a civilized and character-driven society. 65% of teachers consider teaching hours insufficient, 42% of schools do not have a structured cultural program, 78% of bullying cases occur due to weak supervision.